Permainan Ular Tangga Sebagai Alternatif Penyuluhan Kesehatan Gigi Pada Siswa Sekolah Dasar (Jurnal Terapi Gigi dan Mulut, 2023)
Elementary schools that do not yet have the UKGS (School Dental Health Business) program need to hold dental and oral health counseling, but in a fun and interesting way so that the information in it can be absorbed and applied by students. One of the counseling methods is playing snakes and ladders and a spinner board. The game is interesting and innovative. This study aims to determine the effectiveness of counseling using modified media of spinner board and snake ladder games on increasing oral and dental health knowledge in fifth grade students of SDIT Al-Khairiyah Bogor City. This research is quantitative analytic with a quasi-experimental method with a total sample of 20 respondents using total sampling. The results showed that there was an increase in knowledge of oral and dental health after being given counseling using modified spinner board and snake ladder media with an increase in pre-test and post-test scores. The results of the Mann-Whitney test obtained the p< 0.05 (0.001 < 0.05) then H0 is rejected and H1 is accepted so it can be concluded that there is a difference in the effectiveness of the modified media for playing snakes and ladders and spinner board in increasing understanding of oral and dental health in fifth graders of SDIT Al-Khairiyah Bogor City. It is suggested for the school to make a UKGS program by involving the puskesmas and using and developing a modified snake and ladder game in increasing knowledge about health education, especially in dental and oral health.